Uji Efektifitas Daun Kemangi (Ocium basilicum L.) Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Antonius Fransiskus Putra Meliala (Program Studi Farmasi UNAJA, 2023)
The present study investigates the antibacterial efficacy of basil leaves (Ocimum basilicum L.) against the growth of Staphylococcus aureus, a Gram-positive bacterium responsible for various human infections. The increasing resistance of S. aureus to conventional antibiotics has necessitated the exploration of plant-based alternatives with potential antimicrobial activity. Basil leaves are known to contain active phytochemical constituents such as flavonoids, tannins, saponins, and essential oils that may contribute to antibacterial properties. An experimental laboratory study was conducted using a completely randomized design, employing various concentrations of basil leaf extract (10%, 20%, 40%, 80%) tested against S. aureus through the disc diffusion method. Chloramphenicol was used as the positive control, and sterile distilled water as the negative control. The results demonstrated a concentration-dependent antibacterial activity, with the 80% extract exhibiting the largest inhibition zone, though still lower than the zone produced by chloramphenicol. The data were analyzed using one-way ANOVA followed by post hoc Tukey test, indicating significant differences (p < 0.05) among the treatment groups. The findings confirm that basil leaf extract possesses antibacterial activity against Staphylococcus aureus, supporting its potential as a natural antimicrobial agent. These results offer preliminary evidence for the development of phytotherapeutic alternatives in combating bacterial infections, particularly in light of rising antibiotic resistance.